Organic global cryptocurrency: towards a stable international monetary system that is closer to Maqāṣid Sharī'ah - Rahman, Abdurrahman Arum (Islamic economic studies, 2020)
Purpose - The most prominent and persistent problems of our global monetary system are instability and imbalances. We propose an international monetary model to solve these problems while at the same time move the model closer to Maqāṣid Sharīʿah (objectives of Sharīʿah). We name this an organic global monetary model or abbreviated as OGM. OGM is an international monetary model directly built on the national monetary system of each member country so that the two can co-exist. Design/methodology/approach - Model design, theory and literature. Findings - The model can eliminate interest rates at the central bank level, create non-tradable international money, and make a more stable international monetary system. Originality/value - Original.